2015
DOI: 10.1177/0148607114568670
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Arachidonic Acid Deficiency May Contribute to Abnormal Platelet Function During Parenteral Fish Oil Monotherapy in a Piglet Model

Abstract: Using platelet mapping, we have previously shown that neonatal piglets given fish oil monotherapy have abnormal platelet function in the AA pathway. This report demonstrates that such an abnormality can be explained by platelet AA deficiency. Platelet mapping and platelet fatty acid analysis should be undertaken in human infants treated with fish oil monotherapy during PN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…This would certainly be detrimental if the actual preformed AA supply in the emulsion (being 6 × less than the DHA supply) is less than required. In our previous work we proposed a similar mechanism for platelet dysfunction after we showed that provision of FO lipids for 14 days in piglets led to measurable platelet dysfunction associated with reduced tissue (platelet) AA content …”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…This would certainly be detrimental if the actual preformed AA supply in the emulsion (being 6 × less than the DHA supply) is less than required. In our previous work we proposed a similar mechanism for platelet dysfunction after we showed that provision of FO lipids for 14 days in piglets led to measurable platelet dysfunction associated with reduced tissue (platelet) AA content …”
Section: Discussionmentioning
confidence: 85%
“…This translational study adds further information regarding when PN is provided as sole nutrition; both the lipid dose and the lipid composition can have unexpected impacts on neonatal piglet growth, brain size, platelet, and now retinal function . Given that outcomes are improving for young children with intestinal failure, optimizing CNS development and long‐term quality of life need to become key goals.…”
Section: Discussionmentioning
confidence: 97%
“…(40, 41) In addition, long term administration of pure fish oil lipid formulations may increase the risk of essential fatty acid deficiency (42, 43) and coagulopathy (44, 45). …”
Section: Intestinal Failure Associated Liver Disease (Ifald)mentioning
confidence: 99%
“…The manufacturer's label for Omegaven recommends coadministration with emulsions containing n-6 FAs to satisfy EFA requirements and does not recommend fish oil monotherapy. One case study reporting significant bleeding in an infant administered fish oil monotherapy suggested that a lack of ARA metabolites involved in clotting, such as the thromboxane A 2 that is involved in platelet aggregation, could precipitate devastating hemorrhage (89,90). However, although serum levels of LA and ARA do decline during fish oil monotherapy, they do not reach nonsignificant levels and ARA:MA ratios remain stable at ;0.02 (91).…”
Section: Fat Emulsions Used In Pnmentioning
confidence: 99%